Causes and Consequences of Western Extreme Negativism against Islam Will Such Negativism Ever End? How? Why or Why Not? - Ahmed, Ghyasuddin (IIUC Studies, 2015)
Human bad manners of blame games, corruptions, crimes, deceptions, dislikes, greed, hate and turns and twists divide people and create most problems in the society. Since the beginning of industrialization human bad manners have increased many folds in recent years and perhaps reached the highest level resulting in the demise of Soviet communism in early 1990s and the free market economy or capitalism in 2008. After communism Islam became the undeclared enemy of the West that led to the tragic events of terrorism on September 11, 2001. No doubt such heinous acts are absolutely unacceptable and unjust, these gave the few most influential and powerful people in the West to demonize Islam and dehumanize the Muslims for their vested interests. These are the tiny invisible interest groups of who come from different sectors of the society and they always benefit from societal chaos, conflicts, confusions and even wars. Justifiably the West went to war to punish and eliminate the terrorists ignoring totally the other side of story that made Muslim world hostile with the West the Israeli and Palestinian conflict. This is the major cause of Muslim dissatisfaction around the world. To show their anger and dissatisfaction with the USA we saw people dancing and showing their happiness and joy on the streets in the Middle East immediately after destruction of the Twin Towers after the 911 attacks! The truth on Muslim anger was best enumerated by the Pew Research Centers and in a few interviews to the media by a top ranking ex-CIA agent, Michael Scheuer who was assigned to monitor and track bin Laden. In one interview he says, We have yet to find a politician who is willing to tell the American people the truth on the causes that divide the Muslims and the West. Instead of seriously trying to resolve the differences between the Muslims and the West, those tiny but most powerful interest groups are heavily engaged more openly in slandering and smearing Islam and have launched propagandas 24/7 to destroy any good images and names that Islam ever had. This paper discusses the causes and consequences of the prevalence of extreme negativism against Islam in the West through a theory that he calls the Residual Rules. Two systemic models have also been developed to show the various linkages that led to such extreme negativism against Islam. President Clintons recent remark on the Middle East Conflict that Netanyahu killed the peace process and a large section of evangelical US Congressmen are making it impossible to end the conflict. The paper also raised many important issues and suggested few measures to improve relationships between the Muslims and the West. IIUC Studies Vol.9 December 2012: 161-186